Karyotype abnormalities and their clinical signifi cance in a group of chronic myeloid leukemia patients treated with hematopoietic stem cell transplantation - Otero, Luize (2007)
CONTEXT AND OBJECTIVE: Following hematopoietic stem cell transplantation (HSCT), karyotyping is a valuable tool for monitoring engraftment and disease status. Few studies have examined the prognostic signifi cance of karyotypes in patients who underwent HSCT for chronic myeloid leukemia (CML). The objective of this study was to evaluate the signifi cance of pretransplantation cytogenetic status in relation to outcomes following HSCT in CML patients. DESIGN AND SETTING: Case series study at Instituto Nacional do Câncer (INCA), Rio de Janeiro, Brazil. METHODS: Cytogenetic analysis was performed by G banding on 39 patients treated with HSCT. RESULTS: Thirty-one patients were in the chronic phase and eight were in the accelerated phase. Prior to HSCT, additional chromosomal abnormalities on the Philadelphia (Ph) chromosome were found in 11 patients. The most frequent additional abnormality was a double Ph, which was observed in four cases. Following HSCT, full chimeras were observed in 31 patients (79.5%). Among these, 23 (82.3%) had presented Ph as the sole abnormality. Mixed chimeras were observed in seven patients, of which three had additional abnormalities. Only one case did not present any cytogenetic response. Five patients presented cytogenetic relapse associated with clinical relapse following HSCT. Twenty-seven patients are still alive and present complete hematological and cytogenetic remission. CONCLUSION: In our study, the presence of additional abnormalities was not associated with worse outcome and relapse risk. Also, no differences in survival rates were observed. Our study supports the view that classical cytogenetic analysis remains an important tool regarding HSCT outcome.